Investigating temporal change in Fauresmith technology: Insights from Rooidam 2, Northern Cape Province, South Africa - Eltzholtz, Alyssa Kay (Department of Archaeology, 2020)
In southern Africa, stone tool assemblages with both large cutting tools (LCTs) and retouched blanks are ascribed to the Fauresmith Industry, a ‘transitional' industry between the Earlier and Middle Stone Age. ‘Transitional' assemblages are especially relevant for addressing questions concerning the development of increasingly complex behaviors and technological variability associated with later Middle Stone Age assemblages. Few in-situ Fauresmith assemblages have been described, despite the need for a more standardized and behaviorally meaningful understanding of these highly variable assemblages. Rooidam 2 is a pan site lying on the outskirts of Kimberley in the Northern Cape Province, with an excavated sealed and stratified Fauresmith sequence. The site is a suitable choice for investigation, as its sequence spans several strata and the excavated collection has yet to be described or analyzed in any detail. A technological intra-site analysis of ~2000 lithic specimens from Level 5, a dense concentration of artifacts comprised of 10 sub-levels was conducted in order to test for temporal change. Adjacent sub-levels were compared using both quantitative and qualitative data to test for statistically significant changes in the blank production choices and retouched tool morphology within the Fauresmith sequence. The analysis reveals that the Fauresmith assemblage from Level 5 is primarily characterized by centripetally flaked Levallois-like cores, flake and blade blanks, unifacially retouched points, scrapers, and notched pieces. There were no LCTs found in the assemblage, although a single broken fragment with bifacial flaking and a shaped convex edge has a morphology suggestive of a small biface. Although the lithic typology of the analyzed assemblage from Rooidam 2 is generally consistent with Fauresmith assemblages from nearby sites in the Northern Cape, the absence of bifaces and other LCTs is notable. The Rooidam 2 sequence also reflects instances of lithic variability between adjacent sub-levels that may be indicative of a trend towards increased behavioral flexibility in blank production (especially in the frequency of blade and unretouched points), although interestingly there were no significant changes in the retouched tool morphology. The variability within the sequence appears to be isochrestic in nature, and there is no evidence to support either a linear trajectory of lithic complexity or the reality of distinctive temporal phases within the Fauresmith industry at Rooidam 2. The technological characteristics in the assemblage, in addition to the significant instances of variability within the sequence, suggests that the lithic material from Rooidam 2 may be more appropriately described as eMSA rather than Fauresmith.